Feasibility study of small hydroelectric system on terrain elevation differences in an urban catchment - Nurul Ain Abdul Razak (2017)
In ensuring a fully functional and operational mini-hydropower facility, it is crucial to conduct a thorough hydrological study in the proposed geographical area. This serves to ensure that there are sufficient water resources available in the water catchment to allow for a consistent production of hydroelectricity. The frequency analysis is used to examine the reliability of the lowest monthly rainfall which will be used in the design construction of the new water catchment and the mini hydropower. Through the construction of a log-log graph of monthly precipitation against the return period, the projected minimum monthly rainfall can be attained under the stipulated conditions of 1:10, 1:25 and 1:50. Following this, the tabulated values which were projected from the graph as monthly minimum rainfall values will require a form of justification. This was carried out through a series of data analysis based on previous historical records on rainfall patterns and climatic changes. This report ultimately seeks to determine how conservative the tabulated projected minimum monthly rainfall values are following the abovementioned conditions for the construction project.